ANALISIS INTENSITAS KOMUNIKASI GURU DAN SISWA DALAM PELEJARAN EKONOMI UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA KELAS X-A DI SMA KRISTEN PALANGKA RAYA - Annisa Dewita Putri R.; Fendy Hariatama; Grace Evelina Buji; Liling Lenlioni (STKIP Persada Khatulistiwa Sintang, 2025)
Education serves as a primary means to develop competent and competitive human resources. Student academic achievement is a key indicator of educational success, influenced by internal factors such as motivation, interest, and cognitive ability, as well as external factors including the school environment, family support, and teaching strategies. This study aims to examine the relationship between students’ communication skills and academic performance in Economics for class X-A at SMA Kristen Palangka Raya. The research employed observation, interviews, and documentation to evaluate student participation, social interaction, and both verbal and nonverbal communication skills. The findings indicate that teachers play a crucial role in fostering educational interaction through questioning, discussions, and presentations. Student participation increased over time, particularly in group discussions, which encouraged collaboration, empathy, and understanding of economic concepts. Academic achievement showed a positive trend, influenced by communication skills, confidence in speaking, and active engagement in learning. These results highlight the importance of developing communication skills as a strategy to enhance learning quality and academic outcomes. The study is expected to provide valuable insights for teachers, students, and schools in designing more interactive, communicative, and participatory learning methods.